2022
DOI: 10.3390/ijerph19116925
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Socioeconomic Status and Vaccination Uptake: A Study on Influenza Vaccination in a Population-Based Sample

Abstract: Background: Health Literacy (HL) has been recently hypothesized to affect the relationship between socio-economic status (SES) and health conditions. However, to date no study has yet assessed the potential contribution of HL in the pathway through which SES affects influenza vaccination status. We aim to examine the relationships among HL, SES factors, and influenza vaccination uptake in Tuscan (Italy) residents belonging to different high-risk groups (HRGs) for influenza. Methods: The study was performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Previous research on the role of socioeconomic status in predicting influenza vaccination paints a varied picture. Similar to our article, a comprehensive Italian study on health literature and socioeconomic status from 2022, with a smaller sample than the one analyzed in our article (n = 3278), found that those who were not employed or had a poor financial status were significantly more likely to be vaccinated against influenza [38]. A Columbian study, with 2000 people older than 60, reached the same conclusion [45].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous research on the role of socioeconomic status in predicting influenza vaccination paints a varied picture. Similar to our article, a comprehensive Italian study on health literature and socioeconomic status from 2022, with a smaller sample than the one analyzed in our article (n = 3278), found that those who were not employed or had a poor financial status were significantly more likely to be vaccinated against influenza [38]. A Columbian study, with 2000 people older than 60, reached the same conclusion [45].…”
Section: Discussionsupporting
confidence: 83%
“…This is known within the healthcare field as the Reverse Care Law. Research has been carried out specific to influenza vaccination and socioeconomic status, but the results have been contradictory with some studies resulting in both more affluent individuals having lower uptake and others concluding just the opposite [ 37 , 38 ]. In a 2006 study that surveyed 92,101 households across 11 European countries, the data reveal that gender, household income, household size, education level, and population size of the living residence significantly influences the likelihood of becoming vaccinated; however, the results varied and were dependent on each country.…”
Section: Introductionmentioning
confidence: 99%
“…We created a theoretical framework based on the Health Literacy Skills Framework (HLSF), Squiers' [61] and the Paasche-Orlow and Wolf model [62]. Moderators, including both proximal and distal determinants, alongside potential mediators-variables clarifying motives and mechanisms behind outcomes-were considered based on the literature search and according to psychological models, like the Health Belief Model (HBM) [26] and the Protection Motivation Theory (PMT) [27].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Because of this, predictors of vaccine acceptance (like educational levels, socio-economic status, comorbidities, etc) may differ from those of other health behaviors, and personal reasons for getting vaccinated may be dissimilar to those that determine people's decision about healthcare. Similarly, the skills needed to navigate, understand, evaluate, and apply information related to immunization are likely to differ from those needed for other health issues [60,61].…”
Section: Confidence Complacenc Ymentioning
confidence: 99%
“…In the case of COVID-19, this phenomenon might be affected by multiple factors, and theoretically, the factors had been contextualized into three major categories, including poor knowledge of vaccination programs, socioeconomic status, and social interaction. 14 Moreover, recently, influencers in their podcasts discussed the rejection of the COVID-19 vaccine, which is a dilemma that can govern people in society to reject COVID-19 vaccinations, thereby threatening the success of the COVID-19 vaccination program. 15 However, to date, there are no precise data on the prevalence of COVID-19 vaccination refusal and its potential associated factors.…”
Section: Introductionmentioning
confidence: 99%